Preschoolers use phrasal prosody online to constrain syntactic analysis. Issue 2 (14th April 2015) - de Carvalho, Alex; Dautriche, Isabelle; Christophe, Anne
Abstract: Two experiments were conducted to investigate whether young children are able to take into account phrasal prosody when computing the syntactic structure of a sentence. Pairs of French noun/verb homophones were selected to create locally ambiguous sentences ( [la petiteferme ] [est très jolie] 'the smallfarm is very nice' vs. [la petite] [ferme la fenêtre] 'the little girlcloses the window' – brackets indicate prosodic boundaries). Although these sentences start with the same three words, ferme is a noun ( farm ) in the former but a verb ( to close ) in the latter case. The only difference between these sentence beginnings is the prosodic structure, that reflects the syntactic structure (with a prosodic boundary just before the critical word when it is a verb, and just after it when it is a noun). Crucially, all words following the homophone were masked, such that prosodic cues were the only disambiguating information. Children successfully exploited prosodic information to assign the appropriate syntactic category to the target word, in both an oral completion task (4.5‐year‐olds, Experiment 1) and in a preferential looking paradigm with an eye‐tracker (3.5‐year‐olds and 4.5‐year‐olds, Experiment 2). These results show that both groups of children exploit the position of a word within the prosodic structure when computing its syntactic category. In other words, even younger children of 3.5 years old exploit phrasal prosody online to constrain their syntactic analysis. This ability to exploit phrasal prosody to compute syntactic structure may help children parse sentences containing unknown words, and facilitate the acquisition of word meanings. Abstract : In two experiments we investigated whether young children are able to use the position of a word within the prosodic structure to compute its syntactic category (noun vs. verb). Pairs of noun/verb homophones in French were used to create locally ambiguous sentences (e.g. [la petite ferme] [est jolie] the small farm is nice vs. [la petite] [ferme la fenêtre] the little girl closes the window where brackets indicate phonological phrase boundaries). Crucially, all words following the homophone were masked, such that prosodic cues were the only disambiguating information. Children successfully exploited prosody to assign the appropriate syntactic category to the target word in both an oral completion task (4.5‐year‐olds, Experiment 1) and in a preferential looking paradigm with an eye‐tracker (3.5‐ and 4.5‐year‐olds, Experiment 2). Altogether, results show that upon hearing the first words of a sentence, even 3‐year olds exploit prosody online to constrain their syntactic analysis.